Exploring the Impact of Third-Party Funds and Interest Rates on Commercial Bank Lending: A Study of the Indonesia Stock Exchange from 2019 to 2021 - Astuti, Wati Aris; Sellia, Hanna (Faculty of Economics and Business, Universitas Klabat, 2024)
This research aims to examine the exploration of the influence of third party funds and interest rates on commercial bank credit distribution on the Indonesian Stock Exchange 2019-2021. Using quantitative methods with quantitative descriptive types. The sample used was ten banks that had gone public or were listed on the Indonesia Stock Exchange (BEI). The data used in this research are 30 financial reports from the 2019-2021 period, with a purposive sampling technique, using an analytical method, namely the multiple linear regression method which was processed using SPSS v 26. Based on the research results, third party funds have a significant influence on credit distribution with a value of (sig < 0.05) and interest rates do not have a significant influence on credit distribution to commercial banks for the 2019-2021 period (sig > 0.05).